Limited posterior left atrial linear radiofrequency ablation for patients with chronic atrial fibrillation undergoing rheumatic valvular heart surgery - 王均志 杜日映 丁会霞 柏本健 王刚 崔国方 钟志欢 (Chinese medical journal, 2004)
Since 1996, we have begun to successfully treat atrial fibrillation (AF) with the maze procedure, replacing surgical incisions with radiofrequency (RF) ablation.^1,2 Recent data show that the posterior wall of the left atrium seems to be a critical area for the occurrence and the maintenance of AF in patients with valvular heart disease. The objective of this study was to evaluate whether limited surgical RF ablation of the posterior region of the left atrium is safe and effective in curing chronic AF in patients also suffering from valvular heart disease.